Legal Protection for Persons with Disabilities in Palangka Raya - Rollis; Yanatar; Devrayno (Jurnal Ilmu Hukum Tambun Bungai, 2025)
The background of this thesis is the implementation of the right to accessibility for public facilities in Palangka Raya City based on Law Number 8 of 2016 concerning Persons with Disabilities. This study uses a qualitative approach involving primary and secondary data. Primary data was collected through interviews with relevant parties, such as persons with disabilities and local governments. Secondary data was obtained through document and literature studies. The results of the study indicate that the implementation of the right to accessibility for public facilities in Palangka Raya City still faces several obstacles. One significant obstacle is the lack of public awareness and understanding of the importance of accessibility for persons with disabilities. This has resulted in a lack of attention in the planning and construction of disability-friendly public facilities. In order to improve the implementation of the fulfillment of the right to accessibility in public facilities, several recommendations are proposed. First, the Palangka Raya City government needs to increase public awareness through more intensive educational campaigns. Second, adequate budget allocation must be prioritized for the construction and maintenance of accessibility facilities. Third, clear regulations and strict law enforcement must be consistently applied. Fourth, the active involvement of persons with disabilities in planning and evaluation is a crucial step to ensure better fulfillment of the right to accessibility. With better implementation and support from the government and the community, it is hoped that the fulfillment of the right to accessibility in public facilities in Palangka Raya City will improve, creating an inclusive environment, and providing equal opportunities for persons with disabilities.